2015
DOI: 10.1016/j.febslet.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Laminin therapy for the promotion of muscle regeneration

Abstract: a b s t r a c tMuscle regeneration is essentially due to activation of satellite cells, which can be isolated and amplified ex vivo, thus representing good candidates for cell therapy. Accumulating data show that the local microenvironment plays a major role during muscle regeneration. In the satellite cell niche, a major extracellular matrix protein is laminin. Human myoblasts transplanted into immunodeficient mice are preferentially located in laminin-enriched areas. Additionally, laminin-111 enhances myobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The main component of matrigel is laminin, which can mediate the adhesion of myogenic cells through the muscle specific integrin, α7β1 (Yao et al, 1996; Riederer et al, 2015). Laminin is known to be essential for migration and proliferation of murine myoblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The main component of matrigel is laminin, which can mediate the adhesion of myogenic cells through the muscle specific integrin, α7β1 (Yao et al, 1996; Riederer et al, 2015). Laminin is known to be essential for migration and proliferation of murine myoblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the LN α2 chain, which is part of the α2β1γ1 trimer (LN-211), the major LN isoform on muscle, cause severe muscular dystrophy [ 66 ]. Although LN-111 is not present in the normal adult muscle, it is the most studied LN isoform, also applied as a therapeutic agent in different animal models for muscular dystrophies, such as Duchenne muscular dystrophy (DMD) and merosin-deficient congenital muscular dystrophy type 1A (MDC1A) [ 22 , 67 69 ]. Different LN isoforms can have differential effects on myoblast proliferation or differentiation, as shown recently for LN-211 or LN-521 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laminin (LN) and fibronectin (FN) are ECM glycoproteins able to stimulate the migration of different cell types [ 14 – 18 ], including myoblasts [ 19 21 ]. LN is the major glycoprotein of the basal membrane in different tissues, and the isoforms 211 and 221 surrounds the muscle fibers and the SCs [ 22 ]. Although the SC niche does not contain FN, after muscle injury, the expression of this molecule is transiently enhanced, peaking on day 5 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that treatment with natural Englebreth-Holm-Swam (EHS) murine sarcoma derived Laminin-111 enhances muscle regeneration and prevents myopathy of mouse models of LAMA2-CMD and Duchenne Muscular Dystrophy (DMD) [10,11,16,[21][22][23]. To test whether human Laminin-111 has the same effect, we treated NODScid dy W mice with HsLAM-111.…”
Section: Human Laminin-111 and Laminin-211 Protein Therapy Increase Mmentioning
confidence: 99%